Dampak Sosial dan Ekonomi Penggunaan Internet di Komunitas Perbatasan: Studi Kasus di Wilayah Terpencil - Kusnanto Kusnanto; Margaretha Lidya Sumarni; Yulia Rospita Risa (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study analyzes the social and economic impacts of internet use in border communities of Bengkayang Regency, West Kalimantan, involving 70 respondents from diverse backgrounds. The findings show that most respondents use mobile phones primarily for communication, business, entertainment, promotion, and education. The internet is considered beneficial for expanding knowledge, building work relations, and supporting businesses, but challenges include weak signals, high costs, and limited devices. The community expects improvements in network infrastructure, affordable access, and digital literacy training. Adequate internet access has the potential to drive socio-economic development in border areas.